An empirical study on the use of artificial intelligence in the banking sector of Indonesia by extending the TAM model and the moderating effect of perceived trust - Ikhsan, Ridho Bramulya; Fernando, Yudi; Prabowo, Hartiwi; Yuniarty, Y; Gui, Anderes; Kuncoro, Engkos Achmad (Elsevier, 2025)
Artificial intelligence technology is increasingly becoming integral in business, and banks need to implement this technology on a large scale for competitiveness. However, studies on artificial intelligence in the banking sector are limited, and customers are concerned about its implementation. Therefore, this study aims to measure the intention to continue adopting artificial intelligence in Indonesia’s banking sector. This study proposed nineteen hypotheses and used a technology acceptance model framework with the awareness of artificial intelligence, subjective norms, perceived risk, and perceived trust as extensions. The researchers surveyed 388 bank customers who have interacted with artificial intelligence. The survey results extended the technology acceptance model framework by accepting all the hypotheses. This study contributes to the banking industry of developing countries by generating artificial intelligence technology with a high level of security.